KAJIAN SIFAT KIMIA TANAH SAWAH DENGAN POLA PERTANAMAN PADI SEMANGKA DI DESA AIR HITAM KECAMATAN LIMA PULUH KABUPATEN BATUBARA - Junita N Palembang; Jamilah Jamilah; Sarifuddin Sarifuddin (Jurnal Agroekoteknologi, 2013)
Rice and Watermelon cropping pattern has been always applied at Air Hitam Village, Lima PuluhSubdistrict, Batu Bara District. The selected cropping pattern was choosed because of rice productiondid not increase in rice and rice cropping pattern, and it will be expected that rice and watermeloncropping pattern will increase the farmer income. The difference in cropping pattern and supply oforganic matter changes in soil properties of fields. The objective of this study was to know the changesin some chemical properties of paddy soil at Air Hitam Village, Lima Puluh Subdistrict, Batu BaraDistrict which is lacated at about 18 m above sea level (asl). Parameters measured were pH usingElectrometric method, organic carbon by using Walkley and Black method, available phosphorus byusing Bray II method, exchangeable potassium NH4OAc with method, total-N by using Kjeldahl methodand available SiO2 by using ammonium acetate extraction. The results of this study showed that rice andwatermelon cropping pattern didn’t affect the paddy soil chemical properties including pH, organiccarbon, total-N, available phosphorus, and exchangeable potassium, except soil available SiO2, is higherat rice and watermelon cropping pattern compared to that rice-rice cropping pattern.Key words : cropping system, soil chemical properties.